Demonstration and modeling of frequency tripler based on GaN Schottky diode pair. (July 2022) - Zhou, Junmin; Guo, Haowen; Gu, Yitian; Zou, Xinbo
Abstract: Based on GaN Schottky barrier diode (SBD), frequency triplers using anti-parallel diode pair (APDP) are demonstrated and modeled at an output frequency of 3.6 GHz. In addition, two connection schemes, namely series APDP tripler and shunt APDP tripler are explicitly studied and compared. Compared to shunt APDP tripler, series APDP tripler achieved higher output power of −0.14 dBm and smaller minimum conversion loss of 26.9 dB. Precise compact models for both types of triplers were proposed to verify the generation of output power and performance of triplers. In the compact models, nonlinear SPICE parameters of SBD and parasitic parameters of the diode pair were extracted from I–V characteristic and broad band small signal S-parameters. Input and output networks of tripler were de-embedded so that accuracy of harmonic simulations were ensured. The outstanding performance of APDP as a frequency tripler and corresponding models provide a practical option in designing RF multipliers.